Research on the existence of Haemagglutination inhibiting antibodies to porcine parvovirus in pig sera in Greece - ΚΥΡΙΑΚΗΣ, Σ.; ΑΝΔΡΕΩΤΗΣ, Γ.; ΠΑΠΑΣΟΛΩΜΟΝΤΟΣ, Σ.; HENRY, R. R.; ΤΣΑΛΤΑΣ, K. (Journal of the Hellenic Veterinary Medical Society, 2019)
Sera collected from 17 pigs of various ages at a commercial breeder - grower pig farm in Greece have shown antibodies to 59e/63 porcine parvovirus (PPV). The haemagglutination —inhibition titers varied fom 1:640 to 1:16000. The results indicate the existence of PPV in Greece. A future extensive survey of sera collected from different herds of pigs would enlight the distribution of PPV in Greece and its economic significance to the pig industry